2017
DOI: 10.4238/gmr16029666
|View full text |Cite
|
Sign up to set email alerts
|

Identification of reference genes for RT-qPCR analysis in peach genotypes with contrasting chilling requirements

Abstract: ABSTRACT. Selecting and validating reference genes are the first steps in studying gene expression by reverse transcriptase-quantitative polymerase chain reaction (RT-qPCR). The present study aimed to evaluate the stability of five reference genes for the purpose of normalization when studying gene expression in various cultivars of Prunus persica with different chilling requirements. Flower bud tissues of nine peach genotypes from Embrapa's peach breeding program with different chilling requirements were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In addition, GADPH , TEF2, and PLA2 were ranked as the last three in TRV-infected fruits, with GADPH , TEF2, and 18S in different genotypes ( Table 3 ). Although most authors used only a single reference gene as a standardized internal control, it has been suggested that RT-qPCR studies using two or more reference genes may contribute to more reliable results [ 12 , 47 , 48 , 49 ]. According to pairwise variation, two reference genes were required for gene expression level normalization in this study since the V2/3 was lower than 0.15 ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, GADPH , TEF2, and PLA2 were ranked as the last three in TRV-infected fruits, with GADPH , TEF2, and 18S in different genotypes ( Table 3 ). Although most authors used only a single reference gene as a standardized internal control, it has been suggested that RT-qPCR studies using two or more reference genes may contribute to more reliable results [ 12 , 47 , 48 , 49 ]. According to pairwise variation, two reference genes were required for gene expression level normalization in this study since the V2/3 was lower than 0.15 ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported the selection and validation of reference genes in plants [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. However, these reference genes exhibit constant expression patterns under certain experimental conditions, but their expression levels vary widely under other experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…According to the study of Wang et al [91], the reference genes for persimmon under low and high temperature stresses are UBC, RPII and Tua. The most stable genes are ACT and UBQ10 in peaches under chilling stress, thus providing guidelines for more accurate RT-qPCR results [92].…”
Section: Selection Of Internal Reference Genes Under Stressesmentioning
confidence: 99%